2008
DOI: 10.3357/asem.2216.2008
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Respiratory Control and Cerebral Blood Flow Velocity upon Ice-Water Immersion

Abstract: Even without prior cold-water experience, subjects were able to suppress reflex hyperventilation following ice-water immersion, maintaining the cerebral blood flow velocity at a level not associated with impaired consciousness. This study implies that those susceptible to accidental cold-water immersion could benefit from education in cold-shock response and the possibility of reducing the ventilatory response voluntarily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…We make the important addition of a suitable resting cold-water control (i.e., CWI-Rest) and a true thermoneutral resting control (i.e., TN-Rest) in unhabituated persons reflecting the majority of the population. The magnitude of the reduction in MCAv in our resting trial was also similar (i.e., ~6% cf 7%) to that of Mantoni et al [17] who studied resting ice water immersion. However, the present study observed a variation that was larger (SD = 9% cf 4%) and more so during leg only exercise (16%).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…We make the important addition of a suitable resting cold-water control (i.e., CWI-Rest) and a true thermoneutral resting control (i.e., TN-Rest) in unhabituated persons reflecting the majority of the population. The magnitude of the reduction in MCAv in our resting trial was also similar (i.e., ~6% cf 7%) to that of Mantoni et al [17] who studied resting ice water immersion. However, the present study observed a variation that was larger (SD = 9% cf 4%) and more so during leg only exercise (16%).…”
Section: Discussionsupporting
confidence: 62%
“…The inter-individual range in the first two minutes of immersion was also large with a peak reduction of ~23% seen in the CWI-Rest condition and ~35% in the CWI-Kick condition. It may be that those participants who show the greatest reduction in MCAv are most vulnerable to the symptoms of the CSR [17]. These individuals should be targeted for additional protection against the cold if they are at daily risk of accidental water entry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid immersion in cold (0 • C) water results in an immediate increase in HR, respiratory rate, and tidal volume. The hyperventilation leads to decreases in ETCO 2 and cerebral vasoconstriction reflected by a decline of middle cerebral artery velocity and is sufficient to cause disorientation and loss of consciousness (236).…”
Section: Cortical and Neuromuscular Responsesmentioning
confidence: 99%